LncRNA LOXL1‐AS1 regulates the tumorigenesis and development of lung adenocarcinoma through sponging miR‐423‐5p and targeting MYBL2. (23rd November 2019) - Li, Wei; Zhang, Biao; Jia, Youchao; Shi, Hongyun; Wang, Haibo; Guo, Qiang; Li, Hefei
Abstract: Lung adenocarcinoma (LUAD) is the most common form of malignant tumor and closely correlated with high risk of death worldwide. Accumulating researches have manifested that long noncoding RNAs (lncRNAs) are deeply involved in the progression of multiple cancers. LncRNA LOXL1 antisense RNA 1 (LOXL1‐AS1) was identified as an oncogene in several cancers, nonetheless, its biological effect and regulatory mechanism have not been explained in LUAD. Our present study suggested that LOXL1‐AS1 expression was considerably increased in LUAD tissues and cells. Moreover, LOXL1‐AS1 deficiency notably hampered cell proliferation and migration as well as dramatically facilitated cell apoptosis. Through molecular mechanism assays, LOXL1‐AS1 was identified as a cytoplasmic RNA and acted as a sponge of miR‐423‐5p. Furthermore, MYBL2 was targeted and negatively modified by miR‐423‐5p. Rescue experiments revealed that MYBL2 knockdown could counteract miR‐423‐5p repression‐mediated enhancement on the progression of LOXL1‐AS1 downregulated LUAD cells. More importantly, MYBL2 was discovered to interact with LOXL1‐AS1 promoter, indicating a positive feedback loop of LOXL1‐AS1/miR‐423‐5p/MYBL2 in LUAD. These findings manifested the carcinogenic role of LOXL1‐AS1 and LOXL1‐AS1/miR‐423‐5p/MYBL2 feedback loop in LUAD, which could be helpful to explore effective therapeutic strategy for LUAD patients. Abstract : (A) LOXL1 antisense RNA 1 (LOXL1‐AS1) is upregulated in lung adenocarcinoma tissues and cells. (B) LOXL1‐AS1 facilitates cell proliferation and migration as well as suppresses cell apoptosis. (C) LOXL1‐AS1 acts as a sponge for miR‐423‐5p.